Avaliação do mercado de peixes ornamentais em Goiânia e região metropolitana - Araujo, Rafael Martins de (2021)
The objective was to study the production chain of ornamental fish, addressing the retail and consumer trade in Goiânia and the metropolitan area. In general, the variables that characterize the production, trade, marketing chain and the rearing of ornamental fish were analyzed. Questionnaires applied online were used for aquarist practitioners, shopkeepers and producers, and responses were obtained from 82 individuals who fall into the category of aquarism practitioners, 25 shopkeepers and 32 producers. The relationships between the variables were analyzed by the chi-square test, considering 0.05 of significance. The results were compared and evaluated through the confidence interval and highlighted those who had interest within the ornamental fish market. Those individuals who responded as producers demonstrated that they started producing only by hobbie (51.4%) and, with demand growing, their production increased. Shopkeepers, mostly representing pet shops, agricultural shops and water shops have little control of water quality (62.5% of the stores), as well as the watercolor practitioners who, although they have knowledge about water quality (62.3% of the individuals), are few who make this type of evaluation (41.9%). Thus, it was found that, for the most part, the ornamental fish market of Goiânia and the metropolitan region do not actually perform the verification and control of water quality in their places of rearing or selling, either due to lack of knowledge or incentive.